(untitled) (Research, Society and Development, 2020)
The aim of this study was to evaluate the direct effect of Phytogard®, a product based on potassium phosphite, on the development of Phytophthora nicotianae and to verify possible mode of action of this product on the pathogen. The pathogen’s mycelium was exposed to increasing concentrations of Phytogard® and mycelial growth, production of fresh mycelium and zoospores production were evaluated. Regarding the possible mode of action of Phytogard® on P. nicotianae, the hypha morphology, electrolyte leakage, lipid peroxidation, protein synthesis and β-1,3-glucanase activity were evaluated. The pathogen mycelium was inhibited as the phosphite concentration was increased. The production of zoospores was reduced from the lowest concentration of Phytogard® used. There were morphological changes in the pathogen’s hyphae and the electrolyte leakage increased as the concentration of the product increased and over time. There was no difference between treatments in the analysis of lipid peroxidation and total protein. There was a decrease in the activity of the enzyme β-1,3-glucanase as the concentrations of Phytogard® increased. It is concluded that Phytogard® inhibited mycelial growth, production of fresh mycelium and zoospores production of P. nicotianae. Furthermore, the product decreases the thickness of hyphae and increases the number of atrophied ramifications, in addition to harming plasma membrane permeability and cell wall synthesis of the pathogen.